Innovation and financial sustainability in China's long-term care insurance: An empirical analysis of the Nantong pilot - Guo, Peng; Li, Yajun (Frontiers in Public Health, 2022)
Background：Against a backdrop of aging and declining birthrates, the demand for long-term care insurance (LTCI) systems in various countries throughout the world continues to rise. Most traditional LTCI systems only cover a limited group of people, which cannot solve the problem of nursing needs among other groups, and, further, it makes financial sustainability very difficult to achieve. Purpose：This article aims to explore how Nantong successfully achieves both "full coverage" and "financial sustainability" through institutional innovation. Objects: Institutional innovation logic and financial sustainability of LTCI system in Nantong, one prefecture-level city with the highest degree of aging in China. Methods：Through field interviews and research, this article examines the LTCI system in Nantong, exploring its logic and its successful realization of institutional innovation, which combines international and local experience. The study further uses quantitative methods to measure the system’s financial sustainability. Data: From the seventh national population census bulletin, the 13th Five-Year population development plan, the Nantong Municipal Bureau of Statistics and Nantong Statistical Yearbook 2020 from Nantong government. And from the authors’ field survey data in the Medical Insurance Bureau of Nantong. Results：The findings reveal that the Nantong model effectively disperses institutional risks by means of horizontal and vertical transfer payments, diversified financing, and service outsourcing, achieving its dual goals of full coverage and financial sustainability in the long run. Conclusion：Nantong Model has interrupted the path dependence of traditional dual systems and the philosophy of fragmented institutional construction. Nantong’s path-breaking institutional construction paradigm has important theoretical and practical value. Contributions: The experience of Nantong may prove valuable and instructive, for not only other cities in China but also developing countries across the globe.